The Challenge of Indigenous Healing for Global Mental Health - Csordas, Thomas J. (Revista de Antropología Social, 2023)
Psychiatry and anthropology have a long relationship, and it is worth examining aspects of how that relation is carried over into the developing field of Global Mental Health (GMH). One place at which the two disciplines overlap significantly is in addressing religious phenomena and ritual performance in relation to mental health, and one of the greatest challenges for GMH is how productively to take into account forms of indigenous healing based on religion and ritual. In this paper I compare recent texts in GMH written from the standpoint of psychiatry and anthropology, observing that the psychiatric texts emphasize evidence-based determination of treatment efficacy, while the anthropological texts emphasize ethnographic understanding of treatment experience. Reconciling these two emphases constitutes a challenge to the field, attending to contextual variations in treatment events, illness episodes, phenomenological factors both endogenous and intersubjective, and sociopolitical factors both interpersonal and structural. In addressing this challenge, I propose an approach to therapeutic process that on the empirical level can facilitate comparison across the diversity of healing forms, and on the conceptual level can constitute a bridge between efficacy and experience. This approach is predicated on a rhetorical model of therapeutic process including components of disposition, experience of the sacred, elaboration of alternatives, and actualization of change that highlights experiential specificity and incremental change. Deploying this model can help meet the challenge of understanding efficacy and experience in indigenous healing, and prepare the ground for the further challenge of how practitioners of GMH relate to and interact with such forms of healing.
Keywords: anthropology and psychiatry; Global Mental Health; indigenous healing; therapeutic process